2014
DOI: 10.3892/mmr.2014.2266
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the ACE2/angiotensin(1–7)/Mas axis in osteosarcoma cell lines U-2 OS and MNNG-HOS

Abstract: The renin-angiotensin-system (RAS), via its classical angiotensin-converting enzyme (ACE)/angiotensin II/angiotensin II type 1 receptor (AT1R)-axis, is associated with proliferation and metastasis of numerous types of solid tumor. AT1R blockers reduce tumor volume and decrease liver and lung metastasis in murine models of osteosarcoma. Expression and function of the alternative ACE2/Ang(1-7)/Mas axis in osteosarcoma is yet to be studied. In the present study, the basic and interleukin (IL)-1β-stimulated expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(27 reference statements)
1
16
0
1
Order By: Relevance
“…Current evidence supports the idea that both host and tumor RAS are important for tumor growth and angiogenesis in cancer (10,15). As a new part of RAS, the ACE2/Ang-(1-7)/Mas axis also plays an important role in cancer (16,17). Recent studies have shown that low ACE2 expression may be a useful indicator of poor prognosis in HCC and gallbladder cancer (18,19).…”
Section: Discussionmentioning
confidence: 63%
“…Current evidence supports the idea that both host and tumor RAS are important for tumor growth and angiogenesis in cancer (10,15). As a new part of RAS, the ACE2/Ang-(1-7)/Mas axis also plays an important role in cancer (16,17). Recent studies have shown that low ACE2 expression may be a useful indicator of poor prognosis in HCC and gallbladder cancer (18,19).…”
Section: Discussionmentioning
confidence: 63%
“…In another study, IL-1b was able to increase Mas receptor expression and ACE-2 in a concentration-dependent manner in osteosarcoma cells. 36 Use of AT1R antagonist (losartan) did not interfere with IL-1b-induced mRNA for AT1R or other investigated RAS components (Mas receptor, ACE and ACE-2 enzymes) in both fibroblast subtypes. Initially, concentrations of 10 mM were used for losartan as pretreatment.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, it is interesting to point out that IL‐1β stimulation also increased mRNA expression for Mas receptor and ACE, in addition to AT1R in control HPLF in experiments of negative control of gene silencing (data not shown). In another study, IL‐1β was able to increase Mas receptor expression and ACE‐2 in a concentration‐dependent manner in osteosarcoma cells 36 …”
Section: Discussionmentioning
confidence: 93%
“…Ender et al (2014) discovered that the knockdown of Mas expression mediated by small interfering RNA leads to increased cell proliferation in osteosarcoma and suggested that targeting the ACE2/Ang-(1–7)/Mas axis may be beneficial for the treatment of osteosarcoma by reducing cancer cell proliferation and preventing cancer metastasis (Figure 2). …”
Section: Introductionmentioning
confidence: 99%